Pengaruh Job Relevan Information, Partisipasi Anggaran dan Komitmen Organisasi Terhadap Budgetary Slack (Studi pada SKPK Pemerintah Kota Banda Aceh) - Ella Sulfita; Hasan Basri; Faisal Faisal (Program Magister Akuntansi Unsyiah, 2017)
Aimed of the study was to analyze the influence of job relevance information, budget participatory and organizational commitment towards budgetary slack in SKPK (governmental working unit/institution) of Banda Aceh municipality government. The population of the study were head department of finance and treasury at the SKPK of Banda Aceh municipality government. Based on field survey, the number of SKPK in Banda Aceh municipality are 31 working units. This research would considered all the population as part of the respondents which amount of 62 people, thus this research could be classified as the cencus research. The study result showed thatjob relevance information, budget participatory and organizational commitment whether partially or simultaneously had a significant influence towards budget slack at the working units of Banda Aceh municipality government. While, budget participatory had ansignificant influence toward budgetary slack in partially test. In addition, organizational commitment showed similar finding result that provide an significant influence toward the decreasing of budgetary slack at working units in Banda Aceh municipality government. KEYWORDS : Job Relevance Information, budget parcipatory,organizational commitment, and Budgetary Slack